614 Elective Bariatric and Metabolic Surgery in United Kingdom During the Coronavirus Pandemic. (12th October 2021) - Mamidanna, R; Askari, A; Patel, K; Adil, M T; Jain, V; Jambulingam, P; Whitelaw, D; Rashid, F; Munasinghe, A; Al-Taan, O
Abstract: Aim: Elective Bariatric and Metabolic Surgery (BMS) was halted in the UK during the first wave of the Coronavirus (COVID-19) pandemic. Obesity is a predictor of poor outcome in those infected with this virus. This study reports our experience resuming elective weight loss surgery safely amidst the pandemic. Method: Guidance from national bodies (BOMSS/NICE) were reviewed and a Standard Operating Procedure (SOP) was drafted to accommodate local considerations. Data were prospectively collected on patients undergoing BMS following commencement of elective surgery after the first national lockdown. Results: A total of 50 patients underwent BMS at our institution within six weeks of resuming the services. The median age was 41 years old and BMI was 43.8(IQR 40.0-48.8 kg/m 2 ). Equal number of patients underwent laparoscopic Sleeve Gastrectomy (SG) and Roux en-Y Gastric Bypass (RYGB). Of these, 9 patients (18%) had revisional surgery and 48 patients (96%) were discharged within 24 hours of their surgery. The rate of readmission within thirty days of surgery was 6% (n = 3) and 1 patient returned to theatre with an obstruction proximal to the jejuno-jenunal anastomosis. None of the patients exhibited symptoms or tested positive for the COVID-19 virus. Conclusions: With appropriate precautions and protocols, it is feasible and safe to resume BMS, with no increased risk to bariatric patients during the COVID-19 pandemic. This is particularly encouraging for other units in UK to offer BMS after the current lockdown.